Terapi Kognitif Perilaku dan Depresi Pasca Melahirkan - Haerani Nur Haeba; Moordiningsih Moordiningsih (JIP (Jurnal Intervensi Psikologi), 2009)
This study is aimed to discover the effectiveness of cognitive behavior therapy towards post-partum depression. The reseach question of this study is whether or not cognitive behavior therapy can decrease post-partum depression The participants of this study are three mothers who are in the state of seven days to one month of post labour dan obtains a BDt pretest score between 16-23 which indicates moderate depression. Depression is measured with the Beck Depression Inventory. The result of this study shows that cognitive behavior therapy can reduce post-partum depression. The participants whom suffered from moderate post-partum depression showed a difference after acquired such therapy, whereas the participants does not show any symptoms of depression after being treated with cognitive behavior therapy.Keywords: post-labour depression, cognitive behavior therapy, mothers